Nanoparticle Shape Influence over Poly(Lactic Acid) Barrier Properties by Molecular Dynamics Simulations - Baltazar-Rojas, S; Allende-Prieto, S; Torres-Mediano, A; Rojas-Núñez, J (American Chemical Society, 2022)
Climate change is leading us to search for new materials that allow a more sustainable environmental situation in the long term. Poly(lactic acid) (PLA) has been proposed as a substitute for traditional plastics due to its high biodegradability. Various components have been added to improve their mechanical, thermal, and barrier properties. The modification of the PLA barrier properties by introducing nanoparticles with different shapes is an important aspect to control the molecular diffusion of oxygen and other gas compounds. In this work, we have described changes in oxygen diffusion by introducing nanoparticles of different shapes through molecular dynamics simulations. Our model illustrates that the existence of curved surfaces and the deposition of PLA around them by short chains generate small holes where oxygen accumulates, forming clusters and reducing their mobility. From the several considered shapes, the sphere is the most suitable structure to improve the barrier properties of the PLA. © 2022 The Authors. Published by American Chemical Society